A three-equation thermocline thermal energy storage model for bidisperse packed beds. (October 2019) - Odenthal, Christian; Klasing, Freerk; Bauer, Thomas
Highlights: A new more realistic model for bidisperse packings in thermocline thermal energy storage. Four different packings ware simulated in single blow and cyclic operation. The new model is compared to the conventional Schumann model. Up to 6.6 Kelvin temperature differences in single blow and up to 3.5% in cyclic operation. Abstract: The present publication introduces a novel three-equation model for the simulation of bidisperse packed beds, typically utilized in thermocline thermal energy storages with filler. These systems aim for the substitution of a large fraction of cost intensive liquid storage material such as molten salts by a cost effective solid storage material. A higher packing density can be achieved by a combination of large and small particles, i.e. a bidisperse packing. For the simulation of such systems, the currently most widely applied Schumann and continuous solid phase models consider the solid phase as single sized spheres with a mean particle diameter derived from the bidisperse packing. The present work introduces a novel approach, where, besides the differential equation for the fluid, two differential equations for the small and for the large particles are applied. The model is validated with bidisperse experimental data from the literature. For comparison a reference case of a 100 MW electric solar thermal power plant is defined and the bidisperse model is compared to the Schumann model in its outcome for four different particle size combinations. In the single blow operation, where the storage volume is charged from uniform temperature, the temperature curves show differences of up to 6.6 Kelvin. If the thermocline is given time to develop over several consecutive cycles, the difference in charging and discharging time of one period reaches up to 3.5%. With the model presented in this work, accuracy of long duration or annual simulations can be significantly increased.